تأثير التخلّص من الحجم المتبقّي في المعدة مقابل إعادته إليها على معدّل شوارد الدّم وحدوث المضاعفات لدى مرضى الحالات الحرجة(دراسة مقارنة). - غزال, سوسن; زيزفون, حسان; شحود, هديل (Latakia University Journal -Medical Sciences Series, 2016)
إنّ فوائد تطبيق سحب الحجم المتبقّي في المعدة لتقييم أمان التغذية غير واضح ضمن الخطط التمريضية منذ عقود, ويعتمد على الفرضيات فقط، والبيانات العلمية الموجودة لدعم هذه الفرضيات قليلة جداً. وقد أجري هذا البحث نظراً إلى أن لكل وحدة رعاية مركزة خططها الخاصة لتدبير الحجم المتبقي في المعدة, ولا يوجد معايير مُعتَمدة على أبحاث لتدبير الحجوم المتبقية في المعدة من أنابيب التغذية. وحيث تعتبر بعض الأبحاث أن سحب وإعادة الحجم المتبقي في المعدة يمكن أن يؤدي إلى إنسداد أنبوب التغذية, ويعرض المرضى لتلوث محتمل لنظام التغذية. وبالمقابل ترى أبحاث أخرى، أن التخلص من الحجم المتبقي في المعدة قد يعرض المرضى لخطر عدم توازن الشوارد، وربما يغير توازن السوائل أو التغذية. مما يسبب اختلافاً في النتائج البحثية وعليه لا بد من إجراء دراسات أكثر تقارن بين إيجابيات وسلبيات التخلص من الحجم المتبقي في المعدة و إعادته إليها.أجري هذا البحث لتحديد تأثير التخلص من الحجم المتبقي في المعدة مقابل إعادته إليها على مستويات شوارد الدم(الصوديوم, البوتاسيوم)والألبومين، ومعدل حدوث المضاعفات المرتبطة بأنبوب التغذية( انسداد أنبوب التغذية, الإسهال, الاستنشاق الرئوي) لدى مرضى الحالات الحرجة.خطة البحث شبه تجريبية, وأجري البحث على عينة قوامها 30 مريض, في مشفى الباسل بطرطوس. حيث تم جمع البيانات باستخدام أداتين, الأداة الأولى للمعلومات الديموغرافية والطبية, والأداة الثانية استمارة لتقييم الحالة الفيزيولوجية.حدثت المضاعفات في كلتا المجموعتين التجريبيتين, حيث ازداد حدوث المضاعفات الهضمية والميكانيكية والإنتانية في المجموعة التجريبية الأولى, بينما ازدادت المضاعفات الاستقلابية في المجموعة التجريبية الثانية. توصي نتائج هذه الدراسة بإعادة الحجم المتبقي في المعدة بعد سحبه لدى كل المرضى, بينما يُنصح باستخدام طريقة التخلص من الحجم المتبقي في المعدة, فقط في حال تكرار ارتفاع الحجم المتبقي في المعدة, وذلك لمنع حدوث المضاعفات الناجمة عن ارتفاعه.The benefits of the application of the withdrawal of Gastric Residual Volume to evaluate the safety and nutrition is Unclear within the nursing plans for decades, and is based on assumptions only, and scientific data exist to support these hypotheses are very few. Given that each intensive care unit its own plans to measure Gastric residual, and no standards based on research to measure gastric residual volumes from feeding tubes. And Some research Considered That returning gastric residual volume can lead to blockage of the feeding tube, and exposes patients to possible contamination of the feeding system. In contrast, Other research see, Discarding of Gastric Residual Volume may expose patients to the risk of an imbalance of electrolytes, and possibly alter the balance of fluids or nutrition. Causing a difference in the Research results and, therefore, it does not need to conduct more studies comparing the pros and cons of Discarding Versus Returning Gastric Residual Volume. The aim of study was To determine the effect of discarding versus returning gastric residual volume on serum electrolytes (sodium, potassium), albumin, and the occurrence of complications associated with tube feeding (feeding tube obstruction, diarrhea, pulmonary aspiration) among critically ill patients. quasi-experimental research plan, and the research was conducted on a sample of 30 patients, in a AL Basel -hospital in Tartous. data were collected by using two tools, the first tool for demographic and medical information, and the second form tool to assess the physiological condition. Complications occurred in both the two experimental groups, where the increased incidence of gastrointestinal complications, mechanical and infectious in the first experimental group, while the increased metabolic complications in the second experimental group.The results of this study support the recommendation to reintroduce gastric content aspirated with all patients, while advised to discarding gastricresidual volume, just incase of repeated high gastricresidual volume, so as to prevent the occurrence of complications arising from it's increase.